Analysis Of Children Values, Academic Socialization, and Motivation to Continue Junior High School Education - Nayla Humaeda; Alfiasari - Alfiasari (Journal of Child Development Studies, 2016)
The aim of this research was to analyze the value of children, academic socialization, and motivation to continue junior high school education of the school-aged children in rural areas. This research used cross sectional design. The location of the research was determined purposively with the criteria of farming households with a big size of paddy land. The examples of this study were 100 children from complete families whose school-age children were selected by random proportional method. The participants of this research were 100 children from intact families who had children of elementary school selected and choosen by propotional random sampling. Result showed that the value of children was in moderate category for each dimension. There was a significantly positive correlation of dimension academic socialization in discussing between learning strategies and the value of psychological. Meanhile, parent’s academic socialization was in the low category. This means that parents are still lacking in transforming the importance of education to children. The result showed a significant and positive correlation between parent’s academic socialization and child’s motivation to continue education. Parent’s academic socialization also significantly influenced child’s intrinsic motivation to continue education.